Minimally invasive management of renal artery pseudoaneurysm following robotic nephron-sparing surgery: Report of two cases and review of literature - Shahzad S Bulsara; Govind Prasad; Manjubharath; Vinit Paliwal; Tapish Sahu; Virender Sheorain; Tarun Grover; Rajiv Parakh (Indian Journal of Vascular and Endovascular Surgery, 2018)
Partial nephrectomy (PN) either done open, laparoscopic, or robotic is associated with the complication of renal artery pseudoaneurysm (RAP), which is rare but can have grave prognosis. Minimally invasive intervention using endovascular techniques can safely treat this problem with minimal morbidity. We present here two cases of RAP following robotic PN. The first case was a 78-year male patient who underwent robotic PN 3 months prior for a 55 mm × 53 mm clear cell carcinoma of the left lower renal pole. On his 3-month follow-up computerized tomography (CT), he was incidentally diagnosed with a 48 mm × 40 mm × 36 mm well-defined pseudoaneurysm with supply from the lower polar accessory renal artery. The second case was a 42-year male patient who had undergone a robotic PN for a 3.5 cm renal mass. On day 24 postsurgery, he developed hematuria and evaluation with renal CT angiography showed two pseudoaneurysms of approximately 8–9 mm each; associated with a hematoma extending from the mid pole of the left kidney to the tail of the pancreas. We managed to successfully embolize the RAPs endovascularly in both the patients; case one with glue and case two with coils. Both patients were discharged on the next day with no side effects, complications, or morbidity. RAP post-PN; though rare, is a dreaded complication that one should be aware of and be able to treat it timely. Knowing how to managing these situations with minimally invasive techniques should be a part of the armamentarium of all endovascular specialists.